PERBEDAAN PERSEPSI WAJIB PAJAK ORANG PRIBADI PADA KEBIJAKAN SUNSET POLICY DAN TAX AMNESTY: STUDI EMPIRIS DI KANTOR PELAYANAN PAJAK PRATAMA KLATEN - Sulistianingsih, Puji; Trisilo, Rismanto Gatot (KIAT BISNIS, 2016)
The purpose of this research is to know is there any deference between perception of knowledge, attitude, attention, evaluation, motivation, and activity of individual taxpayers on Sunset Policy Volume II Year 2015 and Tax Amnesty Period I (July-September 2016). This research uses quantitative and comparative method by using T test sample pair analysis. The sum of the sample of this research is 100 respondence. The sampling uses convenience sampling method. Research instrument is questionnaire. The result of the research by using T test analysis shows that there are differences between perception of knowledge, attitude, attention, evaluation, motivation, and activity of individual taxpayers on Sunset Policy Volume II Year 2015 and Tax Amnesty Period I (July-September 2016). This is showed by analyzing T test (1) the significancy mark for knowledge is 0,001 which is smaller than level of significancy 0.05 which shows there is different significance of knowledge. (2) The significancy mark for attitude is 0,000 which is smaller than level of significancy 0.05 which shows that there is different significance of attitude. (3) the significancy mark for attention by using T test analysis is 0,000 which is smaller than level of significancy 0.05 which shows that there is different significance of attention. (4) the significancy mark for evaluation by using T test analysis is 0,000 which is smaller than level of significancy 0.05 which shows that there is different significance of evaluation. (5) the significancy mark for motivation by using T test analysis is 0,015 which is smaller than level of significancy 0.05 which shows that there is different significance of motivation (6) the significancy mark for activity by using T test analysis is 0,022 which is smaller than level of significancy 0.05 which shows that there is different significance of activity. Key word: Sunset Policy, Tax Amnesty, Perception, Knowledge, Attitude, Attention, Evaluation, Motivation and Activity